2002
DOI: 10.1182/blood.v99.9.3439
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte survival is promoted by plasma and suppressed by a Bak-derived BH3 peptide that interacts with membrane-associated Bcl-XL

Abstract: Erythrocytes have a defined lifespan in vivo, and the signals that maintain their survival in circulation or trigger their death are unknown. Here, we investigated the control of erythrocyte survival and death in an in vitro culture system where erythrocytes survived for 10 days in serumfree medium in the presence or absence of bovine serum. Death of the cells in culture was correlated with increased exposure of phosphatidylserine and increased levels of intracellular calcium. Cell death could be suppressed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 49 publications
4
29
0
Order By: Relevance
“…In partial agreement with observations by Walsh et al [21], who studied whole red cell population under the same culture conditions, we found that a lower percentage of young, middle aged and old cells could be recovered from cultures in plasma-free medium than from those with plasma. Furthermore, neocytes showed the lowest survival rate at each time point in both culture mediums ( p <0,01) (Fig.…”
Section: Resultssupporting
confidence: 81%
“…In partial agreement with observations by Walsh et al [21], who studied whole red cell population under the same culture conditions, we found that a lower percentage of young, middle aged and old cells could be recovered from cultures in plasma-free medium than from those with plasma. Furthermore, neocytes showed the lowest survival rate at each time point in both culture mediums ( p <0,01) (Fig.…”
Section: Resultssupporting
confidence: 81%
“…To determine the effect of AnkP peptide on the growth and development of P. falciparum, we utilized a recent technique where peptides were delivered into intact RBCs by fusion with the Antennapedia homeoprotein internalization domain (22). Human erythrocytes infected with stage-specific parasites were incubated with 100 -250 M of the fused peptide (AntAnkP).…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were synthesized by fusing with the 16 amino acid internalization sequence of Antennapedia (Ant) homeoprotein, which permits the uptake of peptides into cells via facilitated diffusion (21,22). Human erythrocytes infected with stage-specific P. falciparum were cultured in the presence of Ant-AnkP peptide, the Ant peptide alone, AnkP peptide alone, or a mutant form of the Ant-AnkP peptide where the AnkP portion was scrambled to eliminate the signature sequence of the cleavage site ( Table I).…”
Section: Falcipain-2 Cleaves Erythrocytementioning
confidence: 99%
“…Altogether, these results suggest that the mitochondrial pathway to caspase activation is tightly regulated along the erythroid pathway of differentiation, a regulation that involves Bcl-X L and probably other Bcl-2-related proteins at the mitochondrion level (Aerbajinai et al, 2003). Surprisingly enough, a membrane-associated Bcl-X L was reported also to protect mature erythrocytes, which lack mitochondria, from death (Walsh et al, 2002).…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 92%